Cross country : [compact disc, unabridged] : a novel - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2008)
When the home of Alex Cross's oldest friend, Ellie Cox, is turned into the worst murder scene Alex has ever seen, the destruction leads him to believe that he's chasing a horrible new breed of killer. When the elusive killer's trail turns up in Africa, Alex knows that he must follow. Alone.